Anti-glare coating glass with sol-gel process - Chul Kim, Ki (International Journal of Engineering and Technology, 2018)
Background/Objectives: The next generation car such as self-driving car, and electrical vehicle is a hot issue of the automobile industry, which has the infotainment system with the multi-touch screen panel.Methods/Statistical analysis: The reflection of light from the surface of touch-panel display hinders the clean image acquisition of the display of infotainment system. In this research, anti-glare coating was fabricated by slot die method with the synthesized sols using the TEOS and functional binder on cleaned slide glass. The morphology and surface roughnesswere characterized by FE-SEM, and AFM. The optical properties of anti-glare coating were analyzed by UV-visible spectrophotometer and haze meter.Findings: The average transmittance of anti-glare coating glasses exhibits 88.5% - 90.5% in the visible light range of 400 nm to 800 nm wavelength. The haze value of the anti-glare coating has 7.1% - 36.6% to various coating conditions. The haze values of anti-glare coating were mainly affected by coated sol conditions rather than the coating conditions. The coating conditions of slot die method such as gap distance, and discharge rate of nozzle not affect the quality of anti-glare coating. The haze of anti-glare coating was affected by particle density, and particle size. The anti-glare coating of dense particle distribution and large particle exhibit large haze value about 37%.The best performance of anti-glare coatingwas 7.1% haze, 90.5% average transmittance, and 11 nm average surface roughness, which was coated with the solution #2 sol. The reflectance of anti-glare coating was not affected by change of haze values. But the transmittance of anti-glare coating was affected by haze.Improvements/Applications: The anti-glare coating glass can be applied to various applications such as protective glass of crystalline Si photovoltaic cells, window of skyscraper, and roof of airport buildings.Â